12-267/Homework Assignment 1

From Drorbn
Jump to: navigation, search

This assignment is due at the tutorial on Tuesday September 25. Here and everywhere, neatness counts!! You may be brilliant and you may mean just the right things, but if the your readers will be having hard time deciphering your work they will give up and assume it is wrong.

Question 1. Show that if y=y_1(x) is a solution of y'+p(x)y=0, and y=y_2(x) is a solution of y'+p(x)y=g(x), then for any constant c, y=cy_1+y_2 is a solution of y'+p(x)y=g(x).

Question 2. Solve the following differential equations

  1. For x>0, xy'+2y=\sin x.
  2. \frac{dy}{dx}=\frac{1}{e^y-x} with y(1)=0; you may want to solve for x first.
  3. xy'=\sqrt{1-y^2}.
  4. \frac{dy}{dx}=\frac{x-e^{-x}}{y+e^y}.
  5. xdx+ye^{-x}dy=0, with y(0)=1.
  6. \frac{dy}{dx}=\frac{ay+b}{cx+d}, where a,b,c,d are arbitrary constants.
  7. \frac{dy}{dx}=-\frac{ax+by}{bx+cy}, where a,b,c are arbitrary constants.
  8. 0=(e^x\sin y + 3y)dx + (3(x+y)+e^x\cos y)dy.
Dror's notes above / Student's notes below

Solution to Question 1. Twine

Take y defined by y=cy_1+y_2 and plug it into y'+p(x)y=g(x). We get

(cy_1 + y_2)' + p(x)(cy_1 + y_2) = g(x)

c(y_1' + p(x)y_1) + (y_2' + p(x)y_2) = g(x)

Based on our assumptions about y_1 and y_2, we have y_1' + p(x)y_1 = 0 and we have y_2' + p(x)y_2 = g(x), and so the above equation holds \forall c \in \mathbb{R}.

Hence, \forall c \in \mathbb{R}, cy_1 + y_2 is a solution of y'+p(x)y=g(x).

Solutions to HW1: Mathstudent